Oxidation-Reduction Behaviours, Electrolysis Characteristics and Efficiency of Pd-50at.%Ni Electrode in Alkaline Electrolyte (Journal of Bangladesh Academy of Sciences, 2009)
Convinced on the necessity of finding effective electrodes for electrolyser- the oxidation-reduction behaviors, surface reaction kinetics, stability, electrolysis characteristics and efficiency of a Pd-50at.%Ni electrode have been investigated in 30wt.%KOH electrolyte at room temperature using cyclic voltammetry. Cyclic voltammogram of the electrode showed three couples of oxidation-reduction peaks in between the potential range - 1.0 to + 0.65 V. These peaks were found to be originated from the transformation of zero valent metal to their higher oxides in three consecutive steps and vice versa. The peak potentials, potential differences of the couples and the peak currents were found remarkably different from those of Pd and Ni electrodes. The surface reaction kinetics at Pd-Ni electrode followed the surface reaction trends similar to those of Pd and Ni electrodes. The apparent stability of the electrode was found good. The electrode showed 1.6 and 6.8 times higher oxygen evolution efficiencies than the Ni and Pd electrodes. Addition of Ni with Pd caused hydrogen evolution potentials to move to the negative direction. Tafel plot for the hydrogen evolution reactions (HER) showed two well-defined Tafel regions. Kinetic parameters, i.e., Tafel slope and exchange current density values for the low and high overpotential regions were found 127 mV/dec and 273 mV/dec, and 1.72 x 10-2 mA/cm2 and 1.52 mA/cm2, respectively. Observed slopes indicated its better efficiency over the Pd electrode. Journal of Bangladesh Academy of Sciences, Vol. 33, No. 1, 1-13, 2009 doi: 10.3329/jbas.v33i1.2945